Evolution in subdivided plant populations: concepts, recent advances and future directions. Issue 2 (23rd September 2013) - Pannell, John R.; Fields, Peter D.
Summary: Research into the evolution of subdivided plant populations has long involved the study of phenotypic variation across plant geographic ranges and the genetic details underlying that variation. Genetic polymorphism at different marker loci has also allowed us to infer the long‐ and short‐term histories of gene flow within and among populations, including range expansions and colonization–extinction dynamics. However, the advent of affordable genome‐wide sequences for large numbers of individuals is opening up new possibilities for the study of subdivided populations. In this review, we consider what the new tools and technologies may allow us to do. In particular, we encourage researchers to look beyond the description of variation and to use genomic tools to address new hypotheses, or old ones afresh. Because subdivided plant populations are complex structures, we caution researchers away from adopting simplistic interpretations of their data, and to consider the patterns they observe in terms of the population genetic processes that have given rise to them; here, the genealogical framework of the coalescent will continue to be conceptually and analytically useful. Contents Summary 417 I. Introduction 417 II. Effective population sizes, genetic drift and migration 418 III. Population differentiation, and how best to measure it 420 IV. F ST as a basis of inferring local adaptation: neutral genes vs phenotypes 421 V. Inferring local adaptation: neutral vs selected genes 422 VI. Effects of subdivision on inbreeding and inbreeding depression 424 VII. Current technologies – from genome sequencing to RAD‐tags 425 VIII. Whither now – new wine in old skins? 427 IX. Conclusions 428 Acknowledgements 429 References 429